Bellman-Ford Algorithm for Completion of Route Determination: An Experimental Study - Ari Muzakir; Hutrianto Hutrianto (Universitas Ahmad Dahlan, 2020)
In this study a review of the existing Bellman-Ford Algorithm by conducting tests to see the accuracy of the route data or the shortest route. In this study there are fifth locations that will be tested to see whether the route is really in accordance with the actual situation. The shortest path is part of the field of graph theory. If a graph has weight, then in the case of the shortest route, how can we do the minimization of the total weight of the route. This is what was done in this study to see how optimal the Bellman-Ford Algorithm is in handling the shortest route so that it is more accurate. The fifth Mall data is the most frequently visited by people in the city of Palembang. The five malls are Opi Mall, International Plaza, Palembang Indah Mall, Palembang Square and Palembang Icon. The conclusion from the results of this study is that the Bellman-Ford Algorithm is more complicated to do in the search for calculations manually on the completion of the Traveling Salesman Problem (TSP), but this algorithm is better in terms of finding optimal solutions and solving singe pair routes.